Results from the Population-Based Gutenberg Health Study Revealing Four Altered Autoantibodies in Retinal Vein Occlusion Patients. (29th July 2020) - Bell, Katharina; Beutgen, Vanessa M.; Nickels, Stefan; Lorenz, Katrin; Scheller, Yvonne; Elbaz, Hisham; Peto, Tunde; Ponto, Katharina A.; Schulz, Andreas; Wild, Philipp S.; Münzel, Thomas; Lackner, Karl J.; et al.
Abstract : Purpose . Retinal vein occlusion (RVO) is the second most common retinal vascular disease and a major cause of visual impairment. In this study, we aimed to observe whether RVO cases have different antibody profiles as a new potential risk factor and whether a conversion of retinal vein occlusion (RVO) to neovascular glaucoma (NVG), one of the major complications, is occurring within a 5-year timeframe. Methods . We performed a nested case-control study (1 : 4) within the Gutenberg Health Study (GHS), a population-based, prospective cohort study in the Rhine-Main Region of Germany including 15, 010 participants. RVO subjects ( n = 59) were identified by grading of fundus photographs. Optic nerves of RVO subjects and age- and sex-matched controls ( n = 229) at baseline and their follow-up examination after 5 years were analyzed for glaucomatous alterations. Of all RVO subjects and controls, serum autoantibody profiles were measured using in-house manufactured antigen-antibody microarrays. Results . Of the 59 RVO patients, 3 patients (5%) showed glaucomatous optic disc alterations at baseline, whereas no new glaucoma case was detected at 5-year follow-up. Four of the autoantibodies measured (against dermcidin, neurotrophin-3, superoxide dismutase 1, and signal recognition particle 14 kDa protein) were significantly increased in the serum of RVO patients p < 0.001 . Multivariable conditional logistic regression analysis showed that 3 of these 4 antibodies were independent of cardiovascular risk factors. Conclusions . We found several autoantibodies associated with RVO, targeting proteins and structures possibly involved in RVO pathogenesis.